Clinical anaerobic infections in an Indian tertiary care hospital: A two-year retrospective study. (February 2022) - Angrup, Archana; Sood, Anshul; Ray, Pallab; Bala, Kiran
Abstract: Objective: To study the spectrum of anaerobic infections and the frequency of clinically relevant anaerobes in various infections in a tertiary care hospital in North India. Method: In this two-year (2018–2019) retrospective study, a total of 22, 177 samples were processed both anaerobically and aerobically. The samples included blood, pus, body fluids, necrotic tissues, abscess, peritoneal fluids, and other specimens of conditions predisposing to anaerobic infections. The recovered bacterial isolates were identified by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). Result: Of the 22, 177 samples processed anaerobically, 1094 showed significant anaerobic growth yielding 1464 anaerobes. Bacteroides fragilis (12.7%) and Peptoniphilus harei (12.2%) were the most predominant anaerobes, whereas Escherichia coli (32.6%) and Staphylococcus aureus (13.2%) were the most frequently recovered facultative anaerobes in polymicrobial growth. Both aerobic and anaerobic data were available for 673/1094 samples, of which 68% represented a polymicrobial etiology and 32% as monomicrobial. Of the cases where complete clinical information was available (504/1094), the majority of the anaerobes were recovered from the skin and soft tissue infections (36.3%) and intra-abdominal infections (17.1%). The clinical specimen most frequently growing anaerobes was abscess (29.1%), followed by diabetic foot ulcers (14.1%). Conclusion: The study documents the frequency of clinically significant anaerobic bacteria in various infections, and their associations with aerobes in polymicrobial growth. The present study may aid us in devising better therapeutic strategies against both aerobes and anaerobes in anaerobic infections, which is often empirical. Besides, the data can update clinicians with the changing patterns of anaerobic infections, which remains a neglected concern. Highlights: The high turnaround time complicates the treatment of anaerobic infections. Anaerobic treatment usually remains discretionary, with management often empirical. The infections are generally polymicrobial; therapeutic agent must provide adequate coverage to both aerobes and anaerobes. Frequency of isolation and involvement of anaerobes must be studied periodically in mixed infections. The understanding can help us plan a better therapeutic management of anaerobic infections.